2004
DOI: 10.1002/ana.20315
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglial activation and neuroinflammation in the brain of patients with autism

Abstract: Autism is a neurodevelopmental disorder characterized by impaired communication and social interaction and may be accompanied by mental retardation and epilepsy. Its cause remains unknown, despite evidence that genetic, environmental, and immunological factors may play a role in its pathogenesis. To investigate whether immune-mediated mechanisms are involved in the pathogenesis of autism, we used immunocytochemistry, cytokine protein arrays, and enzyme-linked immunosorbent assays to study brain tissues and cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

100
1,451
6
31

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,844 publications
(1,655 citation statements)
references
References 68 publications
100
1,451
6
31
Order By: Relevance
“…The term cerebral palsy encompasses a group of motor-impairment syndromes that occurs due to injury to the developing brain, which may be associated with deficits in somatosensory perception and/or alterations in the normal development of the somatosensory system (Bax et al, 2005;Wingert et al, 2008). Infection-induced maternal immune activation leads to a fetal inflammatory response mediated by cytokines that has been implicated in the development of not only periventricular leukomalacia and cerebral palsy, but also neurodevelopmental disorders such as autism and schizophrenia (Patterson, 2009;Vargas et al, 2005;Yoon et al, 2000). The timing of the immune challenge with respect to the gestational age and neurologic development of the fetus may be crucial in the response elicited in the neonate (Meyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The term cerebral palsy encompasses a group of motor-impairment syndromes that occurs due to injury to the developing brain, which may be associated with deficits in somatosensory perception and/or alterations in the normal development of the somatosensory system (Bax et al, 2005;Wingert et al, 2008). Infection-induced maternal immune activation leads to a fetal inflammatory response mediated by cytokines that has been implicated in the development of not only periventricular leukomalacia and cerebral palsy, but also neurodevelopmental disorders such as autism and schizophrenia (Patterson, 2009;Vargas et al, 2005;Yoon et al, 2000). The timing of the immune challenge with respect to the gestational age and neurologic development of the fetus may be crucial in the response elicited in the neonate (Meyer et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Elevation, particularly of interleukin-6 and also of other pro-inflammatory markers in the frontal cingulated cortex and CSF, has been described by Vargas et al 17 Patients with regressive autism studied between pre-school age and 12 years old have been shown to have elevated CSF:serum ratios of TNF-␣, interleukin (IL)-1␤, IL-6, and IL 13. 53 Elevation of inflammatory cytokines offers potential therapeutic targets with agents that inhibit cytokine elevations, the use of anti-inflammatory cytokines (such as IL-10), stem cell therapy to re-regulate cytokine dysfunction, and designer drugs of the future that are modeled after these mechanisms.…”
Section: Human Evidence Of Ongoing Atypical Inflammatory Responsementioning
confidence: 84%
“…12 Recent research on postnatal immune issues identify various serum antibodies, as well as cord blood neurotrophins and cytokine levels as potential factors. [12][13][14][15][16][17] Atladottir et al 18 found an increased risk of ASDs in children with a maternal history of rheumatoid arthritis and celiac disease. Also, increased risk of infantile autism was observed for chil-dren with a family history of type 1 diabetes.…”
Section: Part 1: Immune System and Autism: Defining The Relationshipmentioning
confidence: 99%
See 2 more Smart Citations